Exploring Students’ Perspectives On The Use Of Udictionary For Translation - Azra, Tsabitha; Fadihilah, Nurul; Pratama, Ahmad Rizky Ardi; Fahri, Muhammad Aidyl; Waty, Farida Repelita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper reports on a qualitative investigation of several bilingual English-Indonesian students at Medan University in English/foreign language learning. In learning English, students often face difficulties in translating an English text. This challenge arises because students have to understand the meaning of words and sentences in texts that are different from their mother tongue. This difficulty can affect the overall understanding of the text and limit students' ability to interpret the content presented. For this reason, the UDictionary application is being considered as a means for students to assist with translations from the source language to the target language. The author's aim in conducting thisresearch is to try to find out how effective the UDictionary application is in translation as English language learning. With the hope that the author will get results and draw some conclusions from them. The author used qualitative descriptive primary data to obtain results in the form of 30informants who filled out the questionnaire and 5 of the 30 informants who were interviewed. This research shows that using the UDictionary application can help bilingual students in translating English texts, providing learning flexibility and comfort. It is important to consider the use of such applications in English language learning to improve students' understanding and interpretation skills.